The Prevalence of Pediculus capitis Among Schoolchildren in Tripoli Area, Libya - Shibani, Naema; Eman Ghobber; Mohamed Elsaid (AlQalam Journal of Medical and Applied Sciences, 2025)
Pediculus humanus capitis (Head louse) is an obligate ectoparasites that is transmitted from a person to another, through physical contact. Pediculosis is a health problem that is affects schoolchildren in all socio-economic levels. This survey is a descriptive, analytical study carried out to determine the prevalence rate of pediculosis capitis and some associated factors among primary schoolchildren in Tajura and Tripoli cities. The sample size was 4155 randomly selected schoolchildren in urban and rural schools. The survey was carried out for six months. A questionnaire that included questions relating to the age, hygiene, school grade, socio-economic status, parent’s job, level of parent’s education and family size was used. The results of the study showed that 169 schoolchildren (4.1 %) were infested. 0.6 % of the boys and 6.9 % of the girls were infested with head lice. The most prevalent rate was observed in student aged between 9-12 years and the lowest prevalence rate was observed in age group between 5-8 years. There were significant statistical differences between pediculosis capitis and some factors such as sex, level of parent’s education, type of hair (length, colour and thickness), family size, girls wearing scarf and parent’s job (p<0.05). The prevalence rate of head louse infestation in this study was high. The results of the present survey and others in foreign countries show that head louse infestation is a cosmopolitan health problem with different regional prevalence rates rendering it a considerable pediatric problem. يعتبر قمل من الطفيليات الخارجية الذي تنتقل من شخص إلى أخر عن طريق الاتصال الجسدي. القمل يمثل مشكلة صحية تؤثر على أطفال المدارس بجميع المستويات الاجتماعية والاقتصادية. هذا المسح عبارة عن دراسة وصفية تحليلية أجريت لتحديد معدل انتشار قمل الرأس وبعض العوامل المرتبطة به بين أطفال المدارس الابتدائية في مدينتي تاجوراء وطرابلس. تم اختيارالطلبة عشوائياً في المدارس الحضرية والريفية، وبلغ حجم العينة 4155 تلميذاً. تم إجراء الاستطلاع لمدة 6 شهور. حيث استخدام استبيان يتضمن أسئلة تتعلق بالعمر، والنظافة، والصف الدراسي، والحالة الاجتماعية والاقتصادية، ووظيفة الوالدين، ومستوى تعليم الوالدين، وحجم الأسرة. أظهرت نتائج هذه الدراسة أن 169 تلميذاً (4.1%) أصيبوا بالمرض. وكان 0.6% من الأولاد و6.9% من البنات مصابين بقمل الرأس. ولوحظ أن معدل الانتشار كان أكثر لدى الطلاب الذين تتراوح أعمارهم بين 9-12 سنة، ولوحظ أدنى معدل انتشار في الفئة العمرية بين 5-8 سنوات. كانت هناك فروق ذات دلالة إحصائية (P <0.05) بين قمل الرأس وبعض العوامل مثل الجنس، ومستوى تعليم الوالدين، ونوع الشعر (الطول واللون والسمك)، وعدد أفراد الأسرة، وارتداء الفتيات للوشاح، ووظيفة الوالدين. أستنتج ان معدل انتشار الإصابة بقمل الرأس في هذه الدراسة مرتفعا. تظهر نتائج المسح الحالي ومسح آخر في بلدان أجنبية أن الإصابة بقمل الرأس هي مشكلة صحية عالمية مع اختلاف معدلات الانتشار الإقليمية مما يجعلها مشكلة كبيرة للأطفال